Enhancing cold tolerance in tobacco through endophytic symbiosis with Piriformospora indica - Li, Han; Wang, Zhiyao; Yu, Yongxu; Gao, Weichang; Zhu, Jingwei; Zhang, Heng; Li, Xiang; Liu, Yanxia (Frontiers in Plant Science, 2024)
Tobacco, a warm-season crop originating from the Americas, is highly susceptible to cold stress. The utilization of symbiotic fungi as a means to bolster crops' resilience against abiotic stresses has been proven to be a potent strategy. In this study, we investigated the effect of endophytic fungus Piriformospora indica on the cold resistance of tobacco. When exposed to cold stress, the colonization of P.indica in tobacco roots effectively stimulates the activity of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX). This, in turn, reduces the accumulation of reactive oxygen species (ROS), thereby mitigating oxidative damage. Additionally, P. indica elevates the levels of osmolytes, such as soluble sugars, proline, and soluble proteins, thus facilitating the restoration of osmotic balance. Under cold stress conditions, P. indica also induces the expression of coldresponsive genes. Furthermore, this fungus not only enhances photosynthesis in tobacco by stimulating the synthesis of photosynthetic pigments, strengthening Rubisco activity, and elevating PSII efficiency, but also fortifies tobacco's nitrogen assimilation by inducing the expression of nitrate transporter gene and activating enzymes related to nitrogen assimilation. Consequently, this synergistic optimization of nitrogen and carbon assimilation provides a solid material and energetic foundation for tobacco plants to withstand cold stress. Our study demonstrates that a mycorrhizal association between P. indica and tobacco seedlings provides multifaceted protection to tobacco plants against low-temperature stress and offers a valuable insight into how P. indica enhances the cold tolerance of tobacco.